(1,1-Dichloro-2,2,2-trifluoroethylimino) sulfur dichloride, CF3CCl2N=SCl2: Vibrational spectra and quantum chemical calculations - Flores Antognini, Andrea (2009)
The vibrational spectra of (1,1-dichloro-2,2,2- trifluoroethylimino)sulfur dichloride, CF3CCl2N@SCl2, were recorded in the gas phase with IR spectroscopy and in the liquid state with Raman spectroscopy. Quantum chemical calculations at the HF, B3LYP (6-311+G(d) and 6-311+G(2df) basis sets) and MP2 levels of theory (6-31+G(d) and 6-311+G(df) basis sets) were performed. According to all calculations the lowest energy conformer possesses C1 symmetry with syn orientation of the SCl2 group relative to the N-C bondand near-trans orientation of the CF3 group relative to the N=S bond. Calculations predict the presence of a second stable conformer with anticlinal orientation of the SCl2 group which, however, possesses considerably higher energy and is therefore not observed in the analysis of the experimental vibrational spectra. The vibrational spectra were assigned for a single conformer in accordance with these calculations.